Form of Accompaniment Music for H.B.T. Lion Dance Group in Padang City - Zikri Insanillahia, Shuccy; Wimbrayardi (Universitas Negeri Padang, 2023)
This investigation tries to identify the kind of Lion Dance music composition used by the H.B.T. Group in Padang. This kind of research uses content analysis techniques and is qualitative. The researcher is the primary research tool, with aid from other tools like office supplies and cell phones. Observations, interviews, documentation, and literature studies are all used as data collecting approaches. Data analysis involves gathering data, describing data, and drawing conclusions from data. The findings demonstrated that the beat pattern of the lion dance music game is distinct. 11 different repertoires of percussion-based lion dance music exist. However, when all of the repertoires are combined, there are parallels that make lion dance music look like a cohesive whole. This occurs as a result of some repertoires using the same punch motive. Basically, a motif is the combining of multiple notes to produce a specific punch pattern. This makes it necessary to conduct a more thorough analysis of each lion dance music repertoire in order to identify the primary themes and themes that are frequently employed in lion dance performances. It turns out that the 1/8 note motif, which exploits the pace of the lion dance playing style on the 1/16 note, is the most prevalent rhythm pattern motif among the 11 that are performed. Only the voyage of those lion dance types is used in the 1/8 note. In a way, the lion dance's speed is represented by the note 1/16.